86 My watch tells me i have atrial fibrillation! Is that helpful to know?. (8th June 2022) - Chew, Derek; Kuriachan, Vikas
Abstract : Atrial fibrillation (AF) is the most common rhythm disorder encountered in clinical practice. Current prevalence of AF is 1–2%, although the prevalence is increasing in the context of an aging population and growing comorbidities such as obesity and sleep apnea that are risk factors for developing atrial fibrillation. AF is associated with impairment in quality of life and ischemic stroke. The risk of stroke is increased in patients with AF who are also older than 65 years and have risk factors such as diabetes, hypertension, heart failure, and/or prior stroke. Hence with an aging population and increase in obesity, the incidence and prevalence of AF will Fortunately, anticoagulation is the proven method for stroke reduction in patients with atrial fibrillation and a high risk of stroke. Many patients with atrial fibrillation may be asymptomatic and not aware of their dysrhythmia. Additionally, AF can also be paroxysmal or intermittent making detection challenging. These challenges have been mitigated to a degree the development of wearable watches and other monitoring strategies for the general public to screen for atrial fibrillation. However, the link between AF detected by wearables (often short episodes lasting <12 hours) and ischemic stroke is currently unclear. The knowledge gained from cardiac implantable electrical devices, such as implantable loop recorders and pacemakers, on detection of short lasting AF brings in to question the need for AF screening of asymptomatic individuals. The missing link between short-lasting, asymptomatic AF and the ability to modify stroke risk is relevant since anticoagulation can come with an annual risk of 0.5% or more of major bleeding complications along with cost of medications and laboratory testing. A review of the some of the population AF screening technologies, strategies, and published studies will be presented. This presentation will also discuss the available literature around whether population screening for asymptomatic AF will help to decrease the risk of stroke as well as other adverse outcomes associated with AF, such as heart failure and mortality.